DESAIN KENDALI PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO BERBASIS IMPROVED PARTICLE SWARM OPTIMIZATION - Soedibyo Soedibyo; Heri Suryoatmojo (SENTIA 2016, 2016)
This paper presents the modeling and control of excitation through the automatic voltage regulator (AVR) and Govenor through automatic generation control (AGC) or frequency load control (FLC) to increase the stability of micro hydro power (MHP). The three main parts of the generation system is a synchronous generator, AVR / excitation and AGC are modeled linearly. Generators are modeled by a single machine, that is connected to the grid (grid) equipped with AVR and, excitation linear model. Control is done by optimizing, the excitation system AVR, gain (KA) and the AGC gain (Ki) using improved methods of particle swam optimization (IPSO). The main objective of the AVR-AGC gain control is to stabilize the oscillation frequency of the MHP are connected to the grid. Simulations carried out with input step function with load fluctuations 5% as a representation of dynamic loads. The simulation results show that the proposed method effectively raises the level of damping electromechanical oscillations in the MHP and minimize attenuation index of comprehensive (comprehensive damping index / CDI).